Application of satellite images and VNREDSAT-1 images in study on marine environment in Truong Sa region - Cuong, Do Huy; Anh, Bui Thi Bao; Tung, Nguyen Xuan; Luan, Nguyen The; Nam, Le Dinh; Hung, Pham Duc; Nhan, Nguyen Thi; Loi, Tran Xuan (Vietnam Journal of Marine Science and Technology, 2019)
The remote sensing images, including images of MODIS, VNREDSAT-1 and altimeter, are applied for researching marine environment with the different resolutions. On the basis of different time remote sensing images, we concentrated on the assessment of several characteristics including the SST, chlorophyll-a concentration and sea surface current at the different depths in different monsoons as well. With the large areas, we used the images of MODIS and altimeter. The detailed research area focuses on the Nam Yet island, and the images of VNREDSAT-1 are used. The analysis method of environmental parameters of SST and chlorophyll-a used the regression functions based on the single and combined bands to enhance the accuracy of the analysis result. The marine parameters collected at different depths in the latest field surveys on Truong Sa archipelago in the years of 2015 and 2018 are presented in this paper. On the basis of these parameters, we can analyse the relationships and compare the real field survey data and corresponding results interpreted from remote sensing images.